General consulate and honorary consulates of Ukraine in Bulgaria: contribution to development of public diplomacy - Anna Tertychna (Європейські історичні студії, 2019)
The article analyses achievements of the General consulate and honorary consulates of Ukraine in Bulgaria in the field of public and cultural diplomacy, their contribution towards shaping a positive image of Ukraine among the Bulgarian people and intercultural communication between the Ukrainian and Bulgarian people. It focuses on the public activities of the Consulate General of Ukraine in Varna that operated from 2002 till 2014 as well as on the cultural diplomacy activities of the Honorary Consuls of Ukraine in Burgas, Plovdiv and Ruse. It analyses international agreements regulating the activities of the General consulate and honorary consulates in the area of cultural and humanitarian exchange. The article identifies priority areas of support for interliterary, musical and theatrical exchange, which have become dominant in the honorary consulates’ activities. It is important to highlight the assistance of the Honorary Consuls with consolidation and operation of the Ukrainian community in Bulgaria and in uniting the Ukrainian youth.